PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA PADA MATERI PENGURANGAN SEDERHANA KELAS 1 SDN PAKIS V SURABAYA - Kurniasih, Anisah; Eka Pratiwi, Desi; Yuanta, Friendha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aimed to develop Canva-based animated learning media on simple subtraction material for first-grade students at SDN Pakis V Surabaya and determine its validity, practicality, and effectiveness. The research employed the Research and Development (R&D) method using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 37 first-grade students. Data were collected through media expert validation sheets, material expert validation sheets, student response questionnaires, and pre-test and post-test assessments. The results showed that the media obtained validation scores of 100% and 87.5% from media experts and 100% from the material expert. Student responses reached 100% in the very practical category. The N-Gain score was 0.72, indicating a high category. Therefore, the Canva-based animated learning media was proven valid, practical, and effective for teaching simple subtraction in elementary schools